2000
DOI: 10.1038/sj.onc.1203635
|View full text |Cite
|
Sign up to set email alerts
|

Yeast homolog of human SAG/ROC2/Rbx2/Hrt2 is essential for cell growth, but not for germination: chip profiling implicates its role in cell cycle regulation

Abstract: In an attempt to understand the signaling pathway mediating redox-induced apoptosis, we cloned SAG, an evolutionarily conserved zinc RING ®nger gene that, when overexpressed, protects cells from apoptosis induced by redox agents. Here we report functional characterization of SAG by the use of yeast genetics approach. Targeted disruption of ySAG, yeast homolog of human SAG, and subsequent tetrad analysis revealed that ySAG is required for yeast viability. Complementation experiment showed that the lethal phenot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
75
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 63 publications
(77 citation statements)
references
References 83 publications
2
75
0
Order By: Relevance
“…Earlier studies have shown that Hrt1, the yeast homologue of RBX1, is a growth essential gene whose targeted disruption causes yeast death, which can be rescued by either human RBX1 (3,6) or its family member, RBX2/SAG (31). In Caenorhabditis elegans, siRNA knockdown of RBX1 causes pronounced defects in the first meiotic division, in mitotic chromosomal condensation, and in germ cell proliferation, indicating its role in chromosome metabolism and cell cycle control (32).…”
Section: Primary Mef Cells (C) or Es Cells (D)mentioning
confidence: 99%
“…Earlier studies have shown that Hrt1, the yeast homologue of RBX1, is a growth essential gene whose targeted disruption causes yeast death, which can be rescued by either human RBX1 (3,6) or its family member, RBX2/SAG (31). In Caenorhabditis elegans, siRNA knockdown of RBX1 causes pronounced defects in the first meiotic division, in mitotic chromosomal condensation, and in germ cell proliferation, indicating its role in chromosome metabolism and cell cycle control (32).…”
Section: Primary Mef Cells (C) or Es Cells (D)mentioning
confidence: 99%
“…In yeast, deletion of Hrt1, the yeast homolog of RBX1, causes lethality, which can be rescued by human RBX1 or RBX2/SAG (Sensitive to Apoptosis gene) (9,12,13). In Caenorhabditis elegans, RBX-1 is crucial for cell cycle progression and chromosome metabolism, and RBX-1 silencing results in embryonic death (14,15).…”
mentioning
confidence: 99%
“…RBX1 was initially identified as an essential protein for the full activity of SKP1-Cul1-F-Box protein (SCF) E3 ligase, also known as CRL-1, the founding member of CRL (10)(11)(12)(13). SAG, originally cloned in our laboratory, is a redox-inducible antioxidant protein (14) that was later characterized as the second member of the RBX/ROC RING component in SCF/CRL E3s (15). Although RBX1 and SAG are biochemically interchangeable in carrying out E3 ligase activity (15,16), the in vivo physiological functions of both family members was found to be nonredundant.…”
mentioning
confidence: 99%